2016
DOI: 10.1016/j.bbadis.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic signatures of Huntington's disease (HD): 1 H NMR analysis of the polar metabolome in post-mortem human brain

Abstract: Abbreviations:1 H NMR-Proton nuclear magnetic resonance; AD -Alzheimer's disease; AUC -area under the curve; AUROC -area under the receiver operating curve; BBB -blood brain barrier; BCAA -branched-chain amino acid; CNS -central nervous system; CSF -cerebral spinal fluid; DSS -Sodium 2,2-dimethyl-2-silapentane-5-sulfonate; FDR -false discovery rate; fMRI -functional magnetic resonance imaging; GC-Tof-MS -gas chromatography time of flight mass spectrometry; HD -Huntington's disease; IGF-1 -insulin like growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…The decreased BCAA levels were also observed in the CSF of HD subjects [ 138 ]. In line with this evidence, another study identified reduced valine in both the striatum and frontal lobe of HD patients as compared to controls [ 142 ]. Remarkably, plasma BCAA levels were negatively correlated with the severity of motor dysfunction [ 139 ] and the number of CAG repeats in HD [ 139 , 140 ].…”
Section: Altered Bcaas Metabolism In Other Neurological Disordersmentioning
confidence: 57%
“…The decreased BCAA levels were also observed in the CSF of HD subjects [ 138 ]. In line with this evidence, another study identified reduced valine in both the striatum and frontal lobe of HD patients as compared to controls [ 142 ]. Remarkably, plasma BCAA levels were negatively correlated with the severity of motor dysfunction [ 139 ] and the number of CAG repeats in HD [ 139 , 140 ].…”
Section: Altered Bcaas Metabolism In Other Neurological Disordersmentioning
confidence: 57%
“…Topological pathway analysis was performed in MetaboAnalyst to identify the most perturbed biological pathways, as previously described . Briefly, the Rattus Norvegicus library was chosen, and the test for pathway enrichment analysis and relative‐betweenness centrality options for the pathway topology analyses were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this rise, the urea transporter UT-B present in astrocytes is elevated in postmortem human caudate and cortex, possibly to facilitate removal of the excess urea [ 194, 195 ]. A deficit in urea cycle functioning was noted in a prior report demonstrating decreases in post mortem striatal urea indicating additional work is needed to examine enzyme activities and to clarify how the urea cycle may be altered in HD [ 196 ].…”
Section: Energy Deficits In Hdmentioning
confidence: 99%